Impact of the Covid-19 on Transport Sector Activity - Yordanov, Daniel (Research Papers, 2023)
The pandemic of COVID-19 hit Europe at the beginning of 2020 and put the entire population to a huge test, greatly affecting the transport sector. The performance of transport companies is influenced by various factors, most often divided into external and internal. This paper discusses and analyses external factors (macroeconomic conditions, unemployment, legislative and regulatory changes and tax policy) and the extent to which there has been change before and after the COVID-19 pandemic. The aim of the paper is to derive the performance of certain externalities to what extent they are affected by the pandemic based on publicly available information and what impact their magnitudes would have on the transport sector. At the same time, the conclusions from the external factors considered, systematized and analyzed are usually part of any more in-depth business analysis – be it a business plan, financial and economic analysis, development concept, etc.